PENGARUH PELATIHAN, INDEPENDENSI, DAN PENGALAMAN TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (FRAUD) MELALUI SKEPTISISME PROFESIONAL (Pada Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Provinsi Kalimantan Barat) The effect of training, independence, and experience towards auditorâ€™s ability to detect fraud through professional skepticism. (at The Audit Board of Indonesia West Kalimantan Provincial Representative) - B2092172004, ARIANTI (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2020)
This study aims to find out the effect of training, independence, and experience towards auditorâ€™s ability to detect fraud through professional skepticism. Data collection in this study uses a questionnaire distributed to auditors in Audit Board of Republic of Indonesia West Kalimantan Provincial Representative. There were 64 respondents involved in this study. The data were analized by using Partial Least Square (PLS) through SmartPLS software. In addition, sobel test was conducted to axamine the relation of internvening variable within the hypothesis. The results show that experience has a significant effect, while training and independence do not have a significant effect towards auditorsâ€™s ability to detect fraud. This study also shows that independence and experience have significant effects on auditorâ€™s ability in detecting fraud through professional skepticism, yet training has no significant effects on auditorâ€™s ability to detect fraud through professional skepticism.Keywords : Training, Independence, Experience, Professional Skepticism, and Fraud Detection.ReferensiÂ Abdillah, W. & Jogiyanto, H. (2014). Partial Least Square (PLS). Yogyakarta: Andi.ACFE Indonesia Chapter. (2017). Survai Fraud Indonesia 2016. Jakarta: ACFE Indonesia Chapter.Albrecht W.S., Albrecht C. O., Albrecht C. C., & Zimbelman M. F. (2012). Fraud Examination, Fourth Edition. Ohio: South-Western, Cencage Learning.Arbaiti. (2018). Engaruh Pengalaman Auditor, Independensi, Skeptisme Profesional dan Tipe Kepribadian Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan. JOM FEB, Volume 1 Edisi 1 (Januari â€“ Juni 2018).Arep I., & Tanjung H. (2003). Manajemen Sumber Daya Manusia. Jakarta Universitas Trisakti.Arsendy, Muhammad Teguh. (2017). Pengaruh Pengalaman Audit, Skeptisme Profesional, Red Flags, dan Tekanan Anggaran Waktu Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan. JOM Fekon, Vol. 4 No.1 (Februari) 2017.Badan Pemeriksa Keuangan Republik Indonesia. (2017). Standar Pemeriksaan Keuangan Negara. Jakarta: BPK RI.Biksa I. A. I., & Wiratmaja I. D. N. (2016). Pengaruh pengalaman, Independensi, Skeptisme Profesional Auditor Pada Pendeteksian Kecurangan. E-Jurnal Akuntansi Universitas Udayana Vol.17.3. Desember (2016): 2384-2415.Fullerton R. R., & Durtschi C. (2004). The Effect of Professional Skepticism On The Fraud Detection Skills of Internal Auditors. Utah State University.Ghozali, M. I. (2009). Aplikasi Analisis Multivariat Dengan Program SPSS, Edisi Ketiga. Semarang: Universitas Diponegoro.Institut Akuntan Publik Indonesia. (2011). Standar Profesional Akuntan Publik. Jakarta: Salemba Empat.Karamoy H., & Wokas H. R. N. (2015). Pengaruh Independensi dan Profesionalisme Dalam Mendeteksi Fraud Pada Auditor Internal Provinsi Sulawesi Utara. Jurnal Riset Akuntansi dan Auditing â€œGoodwillâ€ Universitas Sam Ratulangi Vol.6, No 2 (2015).Luthans Fred. (2006). Perilaku Organisasi. Edisi Sepuluh, Yogyakarta: PT Andi.Mangkunegara A. P. (2005). Manajemen Sumber Daya Manusia Perusahaan. Bandung : PT Remaja Rosdakarya.Novita U. (2015). Pengaruh Pengalaman, Beban Kerja, dan Pelatihan Terhadap Skeptisme dan Kemampuan Auditor Dalam Mendeteksi Kecurangan. Jom FEKON Universitas Riau Vol.2 No.1 Februari 2015.Oxford University. (1978). The Oxford English Dictionary Volume III. Great Britain: Oxford University Press.Pramana A. C., Irianto G., & Nurkholis. (2016). The influence Of Professional Skepticism, Eksperience And Auditors Independence On The Ability To Detect Fraud. Imperial Journal of Interdisciplinary Research (IJIR), Vol-2, Issue-11, 2016.Singleton T. W., & Singleton A. J. (2010). Fraud Auditing And Forensic Accounting, Fourth Edition. New Jersey: John Wiley & Sons, Inc.Skalak S. L., Golden T., Clayton M., & Pill J. (2011). A Guide to Forensic Accaounting Investigation, Second Edition. New Jersey: John Wiley & Sons, Inc.Suganda, T.R., Ambarwati, Sri, & Astuti, Sri. (2018). Pengaruh Skeptisisme Profesional, Independensi, dan Pengalaman Auditor Terhadap Kemampuan Auditor Mendeteksi Fraud. Jurnal Liquidity: Vol. 7, No. 1, Januari-Juni 2018, hlm. 19-25.Suryanto R., Indriyani Y., & Sofyani H. (2017). Determinan Kemampuan Auditor Dalam Mendeteksi Kecurangan. Jurnal Akuntansi dan Investasi, Vol. 18 No. 1 Hlm: 102-118, Januari 2017.Tuanakotta T. M. (2011). Berpikir Kritis Dalam Auditing. Jakarta: Salemba Empat.Undang-Undang Nomor 15 Tahun 2004 tentang Pemeriksaan Pengelolaan dan Tanggung Jawab Keuangan Negara, Lembaran Negara Republik Indonesia Tahun 2004 Nomor 66.Wiguna F. (2015). Pengaruh Skeptisis,e Profesional dan Independensi Auditor Terhadap Pendeteksian Kecurangan, Survei Pada Auditor KAP Di Malang. e-Proceeding of management: Vol.2, No.1 April 2015 Page 453, ISSN: 2355-9357.